An aesthetics of resilience: design and agency in contemporary coral restoration. Issue 3 (2nd September 2017) - Meyers, Rennie
Abstract: If the Anthropocene points to how human action can destabilise earth's systems, then it also implies that human agency can refurbish and redesign those same systems in the name of mutual survival. On Koh Tao, an island in the Gulf of Thailand, a cohort of tourists and conservationists collect, cultivate, and propagate coral species on artificial reef structures. Koh Tao's economy is dependent on its local reefs to support scuba tourism, but only the New Heaven Restoration and Conservation Program (NHRCP) maintains conservation efforts to support reef resilience and the island's economic health. Its students and instructors re-form their relationship to global climate change as doubly active agents in the Anthropocene: first, claiming responsibility for the ecological impacts of anthropogenic climate change; second, reforming the life-path of coral fragments under new scientific and aesthetic paradigms. As scientists, participants prioritise coral species' genetic diversity and ecological needs. As conservationists, they create narratives that perpetuate investment in resilience. From coral nurseries to underwater sculptures, NHRCP's participants rework their relationship to global climate change and their own sense of agency made manifest through ecological design. They imagine new livelihoods by fashioning resilient, genetically diverse coral species. Their choices become an aesthetic of resilience.